KETOPRAK LESUNG “ CAHYO BUDOYO “ DI DUSUN SIDOWAYAH, HARGOWILIS, KOKAP, KULON PROGO ( SUATU TINJAUAN ASPEK SOSIAL BUDAYA ) - Salim Salim (Akademi Seni dan Desain Indonesia Surakarta, 2014)
Form of art has a function for society in accordance with the natural conditions and the state of social culture where art is born. Sidowayah village communities living in areas far from urban centers or entertainment, with the background of the people whose livelihood as farmers cocoa and palm tapper majority of senior high school education, have some traditional art forms, one of which is Ketoprak Dimples